PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN METAKOGNITIF PADA SISWA KELAS IV SDN 80 PINRANG - Muhammad Nabil; Mutmainnah; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is classroom action research which aims to improve students' Mathematics learning outcomes in class IV at SDN 80 Pinrang using a metacognitive approach. This research was conducted on class IV students in the 2024/2025 academic year odd semester at SDN 80 Pinrang with a total of 26 students consisting of 14 boys and 12 girls. This classroom action research was carried out in 2 cycles, cycle I and cycle II consisting of 3 meetings and 1 final test meeting. Data collection techniques use observation sheets, questionnaires, written tests, and documentation at the end of each cycle according to the material taught. Based on the learning results in cycle I, there were 7 people with around 26.92%. There were 19 students who did not complete the first cycle, around 73.08%, with an average score of 59.84. Meanwhile, there was an increase of 20 students who completed cycle II, around 76.9%, and 6 students who did not complete cycle II increased, around 23.1%, with an average score of 80.34. So it can be concluded that the teaching and learning process can improve the mathematics learning outcomes of class IV students at SDN 80 Pinrang by using a metacognitive approach.